2021
DOI: 10.1289/ehp9449
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sulfur, Transition Metals, and the Oxidative Potential of Outdoor PM2.5 with Acute Cardiovascular Events: A Case-Crossover Study of Canadian Adults

Abstract: Background: We do not currently understand how spatiotemporal variations in the composition of fine particulate air pollution [fine particulate matter with aerodynamic diameter ( )] affects population health risks. However, recent evidence suggests that joint concentrations of transition metals and sulfate may influence the oxidative potential (OP) of and associated health impacts. Objectives: The purpose of the study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 51 publications
(117 reference statements)
1
29
0
Order By: Relevance
“…If the observed health impacts of O x are attributable the combined oxidative nature of the gases themselves, our results have important implications for future regulatory interventions aimed at reducing emissions of individual PM 2.5 components/sources. Specifically, our results suggest that there could be substantial cobenefits to further reductions in transition metals and sulfur in PM 2.5 as these reductions could reduce the health impacts of outdoor PM 2.5 8 as well as the long-term health effects of O x . Of the specific components examined, differences across strata were greatest for Ni and S. Fuel oil combustion is an important source of Ni in PM 2.5 29 and both transportation and industrial sources contribute to sulfur (i.e., sulfate) in PM 2.5 (although sulfur emissions have decreased over time).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…If the observed health impacts of O x are attributable the combined oxidative nature of the gases themselves, our results have important implications for future regulatory interventions aimed at reducing emissions of individual PM 2.5 components/sources. Specifically, our results suggest that there could be substantial cobenefits to further reductions in transition metals and sulfur in PM 2.5 as these reductions could reduce the health impacts of outdoor PM 2.5 8 as well as the long-term health effects of O x . Of the specific components examined, differences across strata were greatest for Ni and S. Fuel oil combustion is an important source of Ni in PM 2.5 29 and both transportation and industrial sources contribute to sulfur (i.e., sulfate) in PM 2.5 (although sulfur emissions have decreased over time).…”
Section: Discussionmentioning
confidence: 86%
“… 1 , 2 , 18 , 19 Sulfur was included in our PM 2.5 component analyses as we recently reported that the acute cardiovascular health impacts of PM 2.5 mass concentrations were stronger in men when both S and transition metals were elevated (S makes the particles more acidic and is thought to make the metals more biologically available). 8 , 20 Therefore, we wanted to examine how combinations of these components may modify the health impacts of O x .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of Canadian hospital admissions found increased cardiovascular events in men associated with Cu, Fe, and Zn exposures when increased sulfur concentrations were also present (e.g., Cu OR = 1.08, 95% CI 1.05–1.11 per 10 μg/m 3 ). 163 …”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…It also reported significant heterogeneity in cardiovascular morbidity with PM 2.5 Fe and Zn (Cochran’s I 2 = 52% and 62%, respectively). A study of Canadian hospital admissions found increased cardiovascular events in men associated with Cu, Fe, and Zn exposures when increased sulfur concentrations were also present (e.g., Cu OR = 1.08, 95% CI 1.05–1.11 per 10 μg/m 3 ) …”
Section: Epidemiological Studiesmentioning
confidence: 99%